The Effect of Online Customer Review, Product Quality and Brand Image on Customer Loyalty with Customer Satisfaction as Intervening Variable Case Study of Somethinc and Skintific Products on Shopee and Tiktok Live Platforms: Conceptual Paper - Ramadhani, Moch. Romy; Widodo, Arry; Rubiyanti, Nurafni; Silvianita, Anita (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores the impact of online customer reviews, product quality and brand image on customer loyalty, with customer satisfaction as an intervening variable, for Somethinc and Skintific products on the Shopee and TikTok Live platforms. Using a quantitative SEM-PLS approach, this study involved respondents aged 18 to 35 years old in Bandung. The findings show that product quality and brand image have a significant influence on customer loyalty, while online reviews provide an indirect influence. Customer satisfaction serves as an important mediator, although it is not always consistent across all variables. The trend of fast beauty and the use of social media are the main factors in making purchasing decisions. This study recommends improving product quality and brand image to maintain customer satisfaction and loyalty.